Hormonal and molecular alterations induced by sub-lethal toxicity of zinc oxide nanoparticles on Oreochromis niloticus - Alkaladi, Ali (Saudi J Biol Sci, 2020)
This study was carried out to determine the biochemical and molecular potential effects of Zn-ONPs sub-lethal toxicity on the hormonal profile of Oreochromis niloticus (O. niloticus). One hundred and fifty O. niloticus juvenile female were used in this experiment; Ninety for determination of LC50 and other 60 fish were divided into 3 groups with 20 fish each (two replicate in each group). Group I used as control group whereas other groups treated with 1/20 and 1/30 of LC50 respectively for 4 days. Serum, pituitary gland, hepatic, pancreatic and muscular tissues were obtained for hormonal and molecular evaluation. Serum growth hormone (GH), thyroid stimulating hormone (TSH), triiodothyronine (T3), tetraiodothyronine (T4), follicular stimulating hormone (FSH), luteinizing hormone (LH), estradiol (E2), testosterone and insulin hormones were significantly decreased with a significant increase in both Adrenocorticosteroid hormone (ACTH) and cortisol levels with no change in serum glucagon levels. On molecular levels there were a significant down regulation in transcriptional levels of GH, Insulin like growth factor I (IGF-I), insulin and Insulin receptor-A (IRA genes. These results suggested that, hormonal and molecular alterations can be used as an early biomarkers for Zn-ONPs toxicity in fish.